FRI0088 Comparison of Rheumatoid Factor, Anti-Citrullinated Protein Antibodies, Anti-Carbamylated Protein Antibody, Anti-Peptidyl Arginine Deiminase Type-3 Antibodies and Calprotectin in Patients with Rheumatoid Arthritis and Spondyloarthritis. (15th July 2016) - Nissen, M.J.; Lamacchia, C.; Bas, S.; Roux-Lombard, P.; Courvoisier, D.; Kyburz, D.; Moeller, B.; Ciurea, A.; Mueller, R.; Zufferey, P.; Bentow, C.; Finckh, A.; et al.
Abstract : Background: A significant proportion of patients with Rheumatoid Arthritis (RA) are negative for rheumatoid factor (RF) and anti-citrullinated protein antibodies (ACPA). There is a unmet need for new biomarkers to better define the severity and prognosis of RA. Objectives: To study the sensitivity and specificity of numerous auto-antibodies and calprotectin in RA patients compared with patients with spondyloarthritis (SpA) and to investigate the relationship between these biomarkes and measures of disease activity and severity. Methods: Data was obtained from the "Swiss Clinical Quality Management" (SCQM) registry which recruits adults with RA, psoriatic arthritis (PsA) and axial spondylarthritis (axSpA). All patients with a Biobank sample were tested for RF (IgM and IgA, QUANTA Flash (QF), Inova), ACPA (anti-CCP2 (Eurodiagnostica) and anti-CCP3 (IgG QF and QUANTA Lite (QL) and IgA QF, Inova), anti-carbamylated proteins (anti-CarP, carbamylated fetal calf serum, prototype ELISA, Inova), anti-peptidyl arginine deiminase type-3 antibodies (anti-PAD3-E.Coli QF and anti-PAD3-insect QF, Inova) and serum calprotectin (QL prototype ELISA, Inova). The control group consisted of patients with PsA (CASPAR criteria positive) and axSpA (ASAS criteria positive). In univariable analyses we tested for associations between the biomarkers and the 28-joint disease activity score (DAS28) and the presence of erosive disease at inclusion. Multivariable analyses were corrected for age, sex, disease duration and anti-CCP2 positivity. Results: A total of 1471 patients were included, 969 with RA and 502 in the SpA control group (317 with axSpA and 185 with PsA). Statistical measures of the biomarkers for the diagnosis of RA are shown in Table 1 . In univariable analyses, RA patients positive for anti-PAD3-E.Coli, anti-PAD3-insect or calprotectin were significantly more likely to have a moderate to high DAS28 (DAS28>3.2) than patients with negative values (68.2% vs. 54.8%, p=0.001, 67.7% vs. 56.0%, p=0.027 and 70.4% vs. 56.2%, p=0.020 respectively). RA patients positive for anti-CarP, anti-PAD3-E.Coli or anti-PAD3-insect were significantly more likely to demonstrate joint erosions compared with patients with negative values (66.3% vs. 57.7%, p=0.037, 68.5% vs. 57.7%, p=0.015 and 71.6% vs. 58.3%, p=0.020 respectively). In multivariable analyses, the odd ratios (and 95% confidence intervals) for the association of anti-PAD3-E.Coli, anti-PAD3-insect or calprotectin with a moderate to high DAS28 were 1.65 (1.15, 2.39), 1.64 (1.02, 2.64) and 1.90 (1.08, 3.35) respectively, and for the association of anti-CarP, anti-PAD3-E.Coli or anti-PAD3-insect with joint erosions were 1.32 (0.90, 1.93), 1.43 (0.95, 2.15) and 1.82 (1.05, 3.15) respectively. Conclusions: Although anti-PAD3 and calprotectin are only present in a minority of RA patients, they are significantly associated with more active disease and anti-PAD3-insect is significantly associated with the presence of joint erosions, independently of ACPA (anti-CCP2). Disclosure of Interest: None declared